2019
DOI: 10.4314/sajas.v49i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transportation and storage duration of Japanese quail eggs on hatchability

Abstract: This study was conducted to investigate the effects of transportation from breeder's farm to hatchery, and of storage duration on the hatchability of quail eggs. Hatching eggs were divided into two groups. The first group was stored for seven days and the second for 14 days. Half of each group was subjected to 200 km transportation before initiation of embryonic development, and the other half was not transported. Relative weight loss ratios varied significantly with storage duration, but did not vary after tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This is in agreement with the reports of Goliomytis et al (2015) and Abioja et al (2020a) . However, Alsobayel et al (2013) reported a decrease in chick yield as length of storage increased from 0 to 14 d. However, Çopur Akpınar and Günenç (2019) discovered that chick yield in Japanese quail was not affected by storage length.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with the reports of Goliomytis et al (2015) and Abioja et al (2020a) . However, Alsobayel et al (2013) reported a decrease in chick yield as length of storage increased from 0 to 14 d. However, Çopur Akpınar and Günenç (2019) discovered that chick yield in Japanese quail was not affected by storage length.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors had confirmed that hatchability is lowered by extended storage of chicken eggs (Petek & Dikmen, 2006;Khan et al, 2014;Abioja et al, 2021), especially in older breeder hens (Tona et al, 2004). A similar report was obtained in studies with quail eggs (Mani et al, 2008;Romao et al, 2008;Çopur Akpınar & Günenç, 2019). The report in a study had stated that hatchable eggs stored for more than 10-14d would have a decline in egg hatchability (King'ori, 2011).…”
Section: Discussionmentioning
confidence: 64%
“…The report in a study had stated that hatchable eggs stored for more than 10-14d would have a decline in egg hatchability (King'ori, 2011). There was a significant difference in hatchability of nontransported Japanese quail eggs stored for 7 or 14d (Çopur Akpınar & Günenç, 2019). There was also a negative relationship between hatchability and egg storage duration (R 2 = 0.53).…”
Section: Discussionmentioning
confidence: 99%
“…With prolonged storage, egg weight loss rates increase, albumen becomes less viscous due to chemical reactions related to moisture and CO 2 loss, causing height reduction, alkalinity increase and palatability loss. According to Akpınar and Günenç (2019), quail eggs can preserve quality attributes at room temperature for storage periods of less than four days. Thus, we hypothesized that the storage of quail eggs under refrigeration reduces the deterioration rate and the eggs can be stored for periods of up to 30 days, under these conditions, without losing internal quality.…”
Section: Introductionmentioning
confidence: 99%